GENETIC VARIATIONS OF IN VITRO PROPAGATED MD2 PINEAPPLES USING DNA-BASED MARKERS - Fifi Hafizzah, Pendi; Hasnain, Hussain; Faisal Ali, Anwarali Khan; Bala, Jamel (Penerbit UMT, 2022)
Genetic variation determinations among micro-propagated plants is often tested to prevent the occurrence of morphological abnormalities which are deemed unsuitable for commercial use. Although the MD2 pineapple has been widely propagated clonally, there is no genetic fidelity testing on the micro-propagated MD2 pineapple. This study aims to determine genetic variations among the micro-propagated MD2 pineapples using Randomly amplified polymorphic DNA (RAPD) and inter simple sequence repeats (ISSR) markers. The amplification of both markers across 22 pineapple genotypes generated 120 bands with polymorphism percentages of between 93% and 73%, respectively. The evaluation through Rp, PIC and MI showed RAPD more informative (Rp = 7.08, PIC = 0.34, MI = 1.72) compared to ISSR (Rp = 4.17, PIC = 0.32, MI = 1.00). The PCA resulted in indefinite clustering patterns while the dendrograms portray the inability of the markers to correlate the plant morphology with their genetic structure. An analysis of molecular variance (AMOVA) analysis found high genetic variation (>70%) within the pineapples under review. Meanwhile, the Phi statistic estimate showed a wide genetic variation among the studied genotypes. To conclude, both markers suggest that the plant morphology did not inevitably correlate to its genetic structure. This study may form the basis for the MD2 breeding programme and explore other molecular markers that can potentially correspond to phenotypic polymorphisms.